Intravascular large B-cell lymphoma presenting with anasarca-type edema and acute renal failure. (September 2013) - Bilgili, Serap Gunes; Yılmaz, Deniz; Soyoral, Yasemin Usul; Karadag, Ayse Serap; Bayram, Irfan
Abstract Intravascular lymphoma (IVL) is a rare extra nodal subtype (usually of B-cell origin) presenting with infiltration of large neoplastic lymphocytes into lumina of blood vessels, leading to vascular occlusion. The early diagnosis is very crucial, however it is usually diagnosed postmortem investigation in most of the cases. A 56-year-old female presented with elevated creatinine level, and anasarca-type edema that superimposed with hard, indurated, erythematous plaques extending to inguinal region, abdomen, anterior aspect of chest, and face. B-cell IVL was confirmed with skin biopsy. The patient had some degree of clinical improvement following chemotherapy. B-cell IVL presenting with anasarca edema was not previously reported in the literature. Even if its rarity, IVL should be considered in the differential diagnosis of renal failure with anasarca edema.